Acid Mine Drainage Treatment Using Bayer Precipitates Obtained from Seawater Neutralization of Bayer Liquor. Issue 12 (21st September 2018) - Kaur, Gurkiran; Couperthwaite, Sara J.; Millar, Graeme J.
Abstract: Bayer precipitates from the seawater neutralization of Bayer liquor waste from the alumina industry are shown to be a prospective solution for the remediation of acid mine drainage (AMD) water. Precipitates are varied in composition, albeit they are generally comprised of hydrotalcite (Mg6 Al2 (OH)16 CO3 ∙ x H2 O), calcite (CaCO3 ), aragonite (CaCO3 ), mixed metal hydroxides (Mg2 Al(OH)7 ), and halite (NaCl). Brucite (Mg(OH)2 ) is detected for lower Bayer liquor concentrations (1–3 g L −1 Al2 O3 ) when the concentrations of aluminum and hydroxyl species are insufficient to promote hydrotalcite formation. The neutralizing capacity of the precipitates also varies with Bayer liquor composition. Treatment of AMD water with Bayer precipitates met discharge pH guidelines. The dissolution of hydrotalcite and brucite (1–3 g L −1 Bayer precipitates only) is responsible for the Bayer precipitate's neutralizing capacity, while calcium carbonate has a buffering affect at around pH 7. Manganese ions are the most challenging species to remove because high pH values are required (pH > 9), which is not possible with all precipitates tested. One caveat is that increasing the degree of manganese removal generates issues with excessive dissolved aluminum which exceeds discharge limits. Future research should address this latter problem and facilitate implementation of this approach to AMD remediation. Abstract : Seawater neutralized supernatant liquor waste from the alumina refining industry is successfully demonstrated to neutralize acid mine drainage water and reduce Fe, Al, Cu, and Zn to within acceptable discharge limits (ANZECC, 2000). The presence of hydroxide and carbonate species in hydrotalcite, and the existence of calcium carbonate species in Bayer precipitates contribute to the treatment of acid mine drainage.